1998
DOI: 10.1007/s002640050200
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in blood vessels entering the growth plate during growth in rats

Abstract: Summary. We observed the structural changes in blood vessels entering the growth plates of the femur and tibia of rats during growth using scanning electron microscopy. The penetrating vessels had blind endings which were bulbous at a time when rats showed rapid skeletal development. With subsequent slowing of development, the density of the vessels decreased and the blind endings became short stumps. These changes were more prominent in the proximal femur than in the distal femur and proximal tibia. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Morgan (1959) also demonstrated that a ring vessel feeds into a lattice-work plexus positioned asymmetrically over the distal half of the growth plate (hypertrophic zone cartilage), making connections to both the metaphyseal and epiphyseal circulations (Irving, 1964). Analyses using scanning electron microscopy of corrosion casts have allowed a third dimension to visualization, but have not challenged the basic concept of the termination pattern of vasculature routes associated with the growth plate (for examples, see Arsenault, 1987;Hunter and Arsenault, 1990;Stanka et al, 1991;Aharinejad et al, 1995;Komuta, et al, 1998). …”
Section: Mpm Imaging Allows Morphological Definition Of Subperichondrmentioning
confidence: 99%
“…Morgan (1959) also demonstrated that a ring vessel feeds into a lattice-work plexus positioned asymmetrically over the distal half of the growth plate (hypertrophic zone cartilage), making connections to both the metaphyseal and epiphyseal circulations (Irving, 1964). Analyses using scanning electron microscopy of corrosion casts have allowed a third dimension to visualization, but have not challenged the basic concept of the termination pattern of vasculature routes associated with the growth plate (for examples, see Arsenault, 1987;Hunter and Arsenault, 1990;Stanka et al, 1991;Aharinejad et al, 1995;Komuta, et al, 1998). …”
Section: Mpm Imaging Allows Morphological Definition Of Subperichondrmentioning
confidence: 99%
“…Finally, the hypertrophic zone, which is closest to the metaphysis, contains chondrocytes that undergo terminal differentiation, cease replication, and enlarge as their cytoplasmic volume swells. This zone plays a key role in the physiological process of endochondral ossification, where vascular invasion at the base of the growth plate stimulates the replacement of cartilage by bone [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Standard histology uses staining to visualise tissue types or tissue components (such as smooth muscle or endothelial cells) in the fracture callus and surrounding tissue [3, 21, 32, 42]. Immunohistochemistry techniques label proteins particular to blood vessels, such as VEGF and CD31, to identify regions of angiogenesis and quantify small vessels [22, 28, 36].…”
Section: Introductionmentioning
confidence: 99%
“…Capillary proliferation around the fracture site has been demonstrated by micro-angiography [29], and vascular budding adjacent to the fracture defect was revealed with contrast perfused histological sections [23]. Electron microscopy [21, 23, 38, 46] and intra-vital microscopy [47, 49] provide high-resolution images that can indicate fine details of the angiogenesis process, such as changes in cell morphology, gene expression or endothelial cell activity. These techniques can indicate fine details of the vessel structure and distribution, but most are two-dimensional and static, providing little quantitative information on blood flow.…”
Section: Introductionmentioning
confidence: 99%